2020
DOI: 10.15585/mmwr.mm6948a5
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Teen Noise Exposure and Efforts to Protect Hearing at School — United States, 2020

Abstract: protection devices (HPDs) during classes or activities where they were exposed to loud sounds, and educational coursework on how to protect their hearing-Porter Novelli YouthStyles, United States, 2020 Characteristic aOR (95% CI) Exposed to loud sounds at school every day/two to four times/week versus never/every few months* School provided HPDs always/usually versus never/seldom † Hearing protection coursework at least once/several times versus never § Sex Male Referent Referent Referent Female 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Recent U.S. studies have associated an increase in teen and young adult hearing loss due to excessive exposure to loud environments and potentially an increased use of personal listening devices. 4 5 Hearing loss in younger age groups can have social and educational implications; so, it will be important to remain watchful of increasing hearing loss rates in future MarkeTrak studies.…”
Section: Comparing Self-reported Hearing Difficultymentioning
confidence: 99%
“…Recent U.S. studies have associated an increase in teen and young adult hearing loss due to excessive exposure to loud environments and potentially an increased use of personal listening devices. 4 5 Hearing loss in younger age groups can have social and educational implications; so, it will be important to remain watchful of increasing hearing loss rates in future MarkeTrak studies.…”
Section: Comparing Self-reported Hearing Difficultymentioning
confidence: 99%
“…Job exposure from noise is historically studied in heavy industry settings but less so in day care or school environments ( Eichwald and Scinicariello 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that not only the industrial or occupational noise exposures, but also the daily noise exposures (such as recreational and public transport noise exposure) may also cause the NIHL [ 5 – 7 ]. In a survey of the adolescent population in U.S., approximately three in four teenage students reported that they were once exposed to loud sound at school, and nearly half (46.5%) of students even reported that they were regularly exposed to loud sounds [ 8 ].…”
Section: Introductionmentioning
confidence: 99%